Le sociologue dans l’action collective face au risque - Marc Mormont (Développement Durable et Territoires)
Risk is a central component of modern industrial societies that have organised complex systems to tackle with them. Environmental problems progressively reveal new risks that are said modern risks because they can be dealt with through usual systems of risk assessment and management. If some authorities still deny these risks, it is important to observe new dynamics that are here described as capture of fear and that are giving strong power to those who are able to propose control systems. These systems can be destructive of many original and creative practices. Sociologist can not be confined in analysis of risk perception, he has to be involved in collective action that try to deal with risks by confronting different collectives and by reorganising them while preserving autonomy.